KAJIAN IMPLEMENTASI PERATURAN MENTERI PERDAGANGAN NOMOR 57 TAHUN 2017 DI BANDAR LAMPUNG - Febrina Veronika Saragih; Zainal Abidin; Ktut Murniati (Lampung University, 2019)
This research was conducted to find out the implementation of Minister of Trade regulation number 57 of 2017 in Bandar Lampung and to determine its supporting and inhibiting factors. This study used a qualitative descriptive method and the research location was chosen purposively with the consideration that Bandar Lampung is an area with high population, economic center, and high consumtion of rice as staple food. The sample size was 25 people consisting of 4 farmers, 2 huller entrepreneurs, 2 large traders, 4 retailers, 12 rice consumers and 1 person as a representative of the food task force. Data collection was conducted in February 2018. The data analysis method used was qualitative descriptive to determine the performance and using Ripley and Franklin's theory to find out the supporting and inhibiting factors. The results showed that the implementation of Minister of Trade regulation number 57 of 2017 in Bandar Lampung was ineffective, although it has supporting factors such as the existence of Standard Operating Procedures (SOP) from the regulations and the establishment of a food task force. Inhibiting factors are the ineffectiveness of the existing food task force, noncompliance of rice business actors, lack of information about policies at the level of rice business actors and the contents of regulations that are not in accordance with the needs of rice business actors.Key words: implementation, regulation, rice, trade